Circular economy in hot-dip galvanizing with zinc and iron recovery from spent pickling acids. Issue 10 (23rd February 2023) - Arguillarena, Andrea; Margallo, María; Arruti-Fernández, Axel; Pinedo, Javier; Gómez, Pedro; Ortiz, Inmaculada; Urtiaga, Ane
Abstract : The management of spent pickling acids (SPA) is an environmental challenge for the hot-dip galvanizing (HDG) industry. We demonstrate at pilot scale the recovery of iron chloride from the SPA of HDG and its reuse at a WWTP facility Abstract : The management of spent pickling acids (SPA) is an environmental challenge for the hot-dip galvanizing (HDG) industry. Bearing in mind its elevated content of iron and zinc, SPA can be regarded as a source of secondary materials in a circular economy approach. This work reports the pilot scale demonstration of non-dispersive solvent extraction (NDSX) in hollow fiber membrane contactors (HFMCs) to perform the selective zinc separation and SPA purification, so that the characteristics needed for use as a source of iron chloride are achieved. The operation of the NDSX pilot plant, which incorporates four HFMCs with a 80 m 2 nominal membrane area, is carried out with SPA supplied by an industrial galvanizer, and consequently technology readiness level (TRL) 7 is reached. The purification of the SPA requires of a novel feed and purge strategy to operate the pilot plant in continuous mode. To facilitate the further implementation of the process, the extraction system is formed by tributyl phosphate as the organic extractant and tap water as the stripping agent, both easily available and cost-effective chemicals. The resulting iron chloride solution is successfully valorized as a hydrogen sulfide suppressor to purify the biogas generated in the anaerobic sludge treatment of a wastewater treatment plant. Additionally, we validate the NDSX mathematical model using pilot scale experimental data, providing a design tool for process scale-up and industrial implementation.